2015
DOI: 10.1007/s00227-015-2719-4
|View full text |Cite
|
Sign up to set email alerts
|

Maternal versus environmental constraints on the oocyte size of a marine pelagophil fish

Abstract: oocyte size are due to a functional relationship between the abdominal volume and ovarian size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
4
0
1
Order By: Relevance
“…More specifically, 10 cm difference in maternal body length corresponded to a 0.030 mm increase in the diameter of hydrated oocytes. Similarly, Ganias et al (2015) found for the Atlantic sardine, Sardina pilchardus, that oocyte size was correlated with maternal size in hydrated ovaries but not in vitellogenic ovaries. The authors suggested that the observed stage-specific differences of the effect of maternal size on oocyte size were due to a functional relationship between the abdominal volume and ovarian size.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…More specifically, 10 cm difference in maternal body length corresponded to a 0.030 mm increase in the diameter of hydrated oocytes. Similarly, Ganias et al (2015) found for the Atlantic sardine, Sardina pilchardus, that oocyte size was correlated with maternal size in hydrated ovaries but not in vitellogenic ovaries. The authors suggested that the observed stage-specific differences of the effect of maternal size on oocyte size were due to a functional relationship between the abdominal volume and ovarian size.…”
Section: Discussionmentioning
confidence: 65%
“…Variability in the weight of hydrated ovaries (Zwolinski et al, 2001) and in the growth patterns of hydrated oocytes (Ganias et al, 2011) have been used however to assess the daily spawning patterns of sardine off the Iberian peninsula. Both papers suggested synchronization of FOM amongst imminent spawners which helped elucidating the daily spawning pattern of the population (Bernal et al, 2011) and disentangling maternal effects on egg size (Ganias et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…F POF was given as Nv i times ovary volume (OV). OV was estimated by dividing OW by the assumed ovarian specific gravity, set to 1.026 for both species (Ganias et al, 2015). RF POF was thereafter calculated (see previous paragraph).…”
Section: Pof Fecundity Using the Weibel Methodsmentioning
confidence: 99%
“…La variabilidad en la producción (cantidad) y calidad (tamaño) ovocitaria en individuos de la misma especie ha sido investigada, concluyendo que la condición maternal es determinante en el éxito reproductivo y esta a su vez puede verse afectada por factores ambientales y antrópicos (Saborido-Rey, 2004;Alonso-Fernández y Saborido-Rey, 2011;Cooper et al, 2013;Ganias et al, 2014Ganias et al, , 2015. Altos niveles de explotación pesquera pueden modificar la estructura de tallas de la población haciendo que el potencial reproductivo del stock disminuya desproporcionadamente (Berkeley et al, 2004;Wright y Trippel, 2009) y esos cambios impactan considerablemente las estimaciones del estado anual de la fecundidad (Cooper et al, 2013).…”
Section: Discusión Y Conclusionesunclassified